Улетают - улетели: стихи / Е. А. Благинина ; художник С. Остров - Благинина Елена Александровна (Малыш, 1982)
Экземпляры: ДО (20190208) / Инвентарный номер: 3769 / Цена: 01.10 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: Б 68 / ГРНТИ: 17.82.93 / ББК: 84(2Рос=Рус)6